Easy and direct conversion of tosylates and mesylates into nitroalkanes - Palmieri, Alessandro; Gabrielli, Serena; Ballini, Roberto (Beilstein Journal of Organic Chemistry, 2013)
Tosylates and mesylates were directly converted into the corresponding nitroalkanes, by their treatment with tetrabutylammonium nitrite (TBAN) under mild conditions.
Keywords: mesylates; nitroalkanes; nucleophilic substitution; tetrabutylammonium nitrite; tosylates